Immunized witness (state's witness) in criminal legislation of Bosnia and Herzegovina - Damir Primorac (Zbornik Radova Pravnog Fakulteta u Splitu, 2013)
International community, considering all dangers generated by aggravated forms of criminality getting more of transnational characteristics on yearly basis, and representing a permanent danger for citizens on national, regional and global level, is trying to develop legal mechanisms and respond to mentioned threats in the most efficient way. One of the modern ways to fight organized criminal groups allows the prosecutor to, under some conditions, refrain from legal criminal processing, what is certainly an exception and is used when required by a public interest: that is giving immunity in the criminal procedure. Besides large efforts there are huge problems faced in practice as mentioned persons (the ones getting the immunity) are more than often trying to dupe the judiciary; sometime it works in legal systems with superficial and unclear legislation. The purpose of this paper is to highlight such type of deficiencies in the legal system of Bosnia and Herzegovina by presenting eventual solutions in the positive regulations, particularly solutions in the neighbor countries which showed to be very efficient.